Soluble Adhesion Molecules Correlate with Surface Expression in an In Vitro Model of Endothelial Activation. (6th July 2013) - Kjærgaard, Anders G.; Dige, Anders; Krog, Jan; Tønnesen, Else; Wogensen, Lise
Abstract: Endothelial activation is a pivotal event in the development and progression of inflammation. Central to endothelial activation is the up‐regulation of cellular adhesion molecules (CAMs) including E‐selectin (CD62E), ICAM‐1 (CD54), VCAM‐1 (CD106) and PECAM‐1 (CD31). These CAMs are also found in soluble forms (sCAMs). In this in vitro study of endothelial activation, we examined whether the levels of sCAMs correlate with the endothelial surface expression of CAMs in a dose‐dependent and time‐dependent manner. Such a correlation would support the use of sCAMs as surrogate markers for endothelial activation in inflammatory conditions. Human umbilical vein endothelial cells (HUVEC) were cultured with various concentrations of TNF‐α for 8 hr and at a fixed concentration of TNF‐α for various durations. The levels of soluble and surface‐bound E‐selectin, ICAM‐1, VCAM‐1 and PECAM‐1 were quantified by flow cytometry. TNF‐α stimulation increased CAM and sCAM expression in a dose‐dependent and time‐dependent manner. There was a significant positive correlation between the levels of ICAM‐1 and sICAM‐1 and between the levels of VCAM and sVCAM‐1 in both the dose–response and time–response experiments. A positive correlation between the levels of E‐selectin and sE‐selectin was observed in the time–response experiment. This study supports the use of sCAMs as potential biomarkers of endothelial activation. In particular, the use of sICAM‐1, sVCAM‐1 and sE‐selectin seems promising.